2017
DOI: 10.3390/su9071086
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Land-Use Planning to Improve the Coastal Resilience of the Social-Ecological Landscape

Abstract: The dynamics of land-use transitions decrease the coastal resilience of the social-ecological landscape (SEL), particularly in light of the fact that it is necessary to analyze the causal relationship between the two systems because operations of the social system and the ecological system are correlated. The purpose of this study is to analyze the dynamics of the coastal SEL and create a sustainable land-use planning (SLUP) strategy to enhance coastal resilience. The selected study site was Shindu-ri, South K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 46 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…In general, papers using modelling are based on the exploitation of a resource stock by methods such as fishing [52], forest management [53], and agricultural production [54]. However, Kim et al (2017) [55] also assessed modelling by addressing three issues that they identified in their study area: coastal landscape management, agricultural structure, and tourism industry structure. This method provides a way to test the system for tipping points without putting the actual system at risk [56].…”
Section: Modelsmentioning
confidence: 99%
“…In general, papers using modelling are based on the exploitation of a resource stock by methods such as fishing [52], forest management [53], and agricultural production [54]. However, Kim et al (2017) [55] also assessed modelling by addressing three issues that they identified in their study area: coastal landscape management, agricultural structure, and tourism industry structure. This method provides a way to test the system for tipping points without putting the actual system at risk [56].…”
Section: Modelsmentioning
confidence: 99%
“…On the other hand, it has also decreased the quality of the coastal landscape. As a result, this deterioration of the landscape has reduced the structure of the tourism industry [27,63]. Although regional activities and festivals were assessed mostly in terms of economic factors in planning studies regarding festivals, visitors, and tourism, they are obviously important in terms of tourist use today [63].…”
Section: Discussionmentioning
confidence: 99%
“…This method was later developed by Nijkamp et al [63]. It is based on making a preference by comparing the alternatives in a systematic analysis [64,65].…”
Section: Elimination and Choice Expressing Reality (Electre)mentioning
confidence: 99%
“…Resilience can be understood as the capacity of systems to maintain a basic structure and function after being disturbed, which emphasizes the adjustment and adaptation of human society in the context of environmental changes and provides a basic logical framework for the study of human-land relations [19][20][21]. The definition of SELPR is the capacity of SELPs to withstand disturbances without changing the system state [12,13,22]. Compared with traditional social-ecological resilience evaluation, the outstanding characteristics of SEPLR evaluation are represented by the spatial representation of landscape system elements and the quantitative characterization of resilience heterogeneity [23][24][25].…”
Section: Introductionmentioning
confidence: 99%